Draft Annual Plan 2004-2005 (Sectoral Plans) Volume-II Government of Nagaland - Planning Commission (Planning Commission, 2004)
The Department of Science and Technology in the State started functioning as a full fledged department in 1992 and since then the activities of the department has greatly increased. The activities proposed to be taken up during the 10th plan period will broadly cover the following areas I) S and T popularization II) Research and Development projects on both S and T sector and Ecology and Environment III) New and viable projects on Non conventional Sources of Energy and IV) Promotion and development of Information Technology (IT) activities which will include creation of IT infrastructure in the state and V) Bio-technology projects.
Government of Nagaland, Planning and Co-ordination Department
Planning and Co-ordination Department Government of Nagaland